Effects of Self-Expressive Brand and Susceptibility to Interpersonal Influence on Brand Addiction: Mediating Role of Brand Passion - Bai, Shizhen; Yin, Yue; Yu, Yubing; Wei, Sheng; Wu, Rong (Frontiers in Psychology, 2021)
Although the concept of the consumer–brand relationship has undergone rapid change over the past two decades, the issue of brand addiction is still generally neglected in the literature. Drawing on identity theory, this research develops a conceptual model of the influence of self-expressive brands (SEBs) and susceptibility to interpersonal influence (SUSCEP) on brand addiction. The results of this research demonstrate both separate and joint effects of SEBs and SUSCEP on brand addiction. In addition, harmonious brand passion and obsessive brand passion positively mediate the relationships among SEB, SUSCEP, and brand addiction. This research introduces a new perspective on the formation mechanism of brand addiction and has important practical implications for brand marketers concerned with finding the most effective means to enhance the consumer–brand relationship.